PERNIKAHAN DALAM MAHRAM MUSHAHARAH DI DESA MEKARJAYA KECAMATAN BUAY PEMACA KABUPATEN OKU SELATAN - Annisa Nurbaiti; M Tamudin; Sandy Wijaya (Program Studi Al-Ahwal Al-Syakhshiyyah, 2021)
Marriage in mahram mushaharah is a marriage that is prohibited in Islam according to the word of Allah SWT. in Qs.An-Nisa verse 23 about mahram muabbad which means people who are forbidden to be married forever. However, marriages in this mushaharah mahram are still found in Mekarjaya Village, Buaypemaca District, South OKU Regency. This research is a field research that is conducting interviews and direct observations of the object of research using a qualitative approach. And supported by primary and secondary data sources. All the data is arranged systematically and then a conclusion is drawn in relation to the problem under study. Marrying a stepdaughter is not allowed under Islamic law, if there has been dukhul with his biological mother, as in the opinion of the majority of scholars. Meanwhile, Ibn Hazm has another opinion, namely that it is permissible to marry a stepdaughter even though there has been dukhul as long as the stepchild is not under the care of his stepfather. As Ibn Hazm has stated in his book Al-Muhalla bil Atsar that the cause of kemahraman between the stepchild and his stepfather if it has fulfilled two absolute conditions simultaneously, namely dukhul and hujur. If one of them is not fulfilled, then it cannot be said to be a mahram. So that his stepdaughter is lawful for his stepfather to marry. As in the case that the researcher has encountered, the marriage of Tejo and Tiwi when viewed from Ibn Hazm's opinion is legally permissible. While the marriage of Yanto and Yuna is not allowed/forbidden, both according to the opinion of the majority of scholars and Ibn Hazm.